Albert Park. A world in a city block (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2018)
Literature on South African cities walks a tightrope between extreme imagery of both hope and despair. This essay aims to discuss some complexities in relation to Albert Park, located in the port city of Durban on South Africa’s east coast. Like all South African cities, Durban remains a concrete manifestation of past apartheid segregation policies, but the built environment is also being shaped by new forms of social and political relations. So the text offers to the reader an overview of the built environment and social relations within this particular urban space. In doing so it outlines how particular groups of people have been popularly linked to urban decay both in the past and in the contemporary.